2021
DOI: 10.3389/fendo.2021.625457
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Mineralocorticoid Receptor Antagonists in Primary Aldosteronism

Abstract: ObjectiveTo investigate how often target renin is pursued and achieved in patients with primary aldosteronism (PA) and other low renin hypertension (LRH) treated with mineralocorticoid receptor antagonists (MRAs), as reversal of renin suppression was shown to circumvent the enhanced cardiovascular and renal morbidity and mortality in these patients.Patients and MethodsWe conducted a retrospective cohort study of patients with PA and LRH treated with MRAs in an academic outpatient practice from January 1, 2000,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…More aggressive up-titration of MR antagonists has been shown to provide greater improvements in BP and albuminuria ( 30 ) and may have led to improvements in subclinical systolic dysfunction in our patients. It has to be noted that medical treatment may be fraught with dose-limiting side effects, leading to suboptimal dosages and efficacy, as other investigators ( 31 ) and we have previously reported ( 32 ). Finally, current MR antagonists may not completely block aldosterone effects or concomitant glucocorticoid excess, which can occur in PA ( 13 ).…”
Section: Discussionmentioning
confidence: 57%
“…More aggressive up-titration of MR antagonists has been shown to provide greater improvements in BP and albuminuria ( 30 ) and may have led to improvements in subclinical systolic dysfunction in our patients. It has to be noted that medical treatment may be fraught with dose-limiting side effects, leading to suboptimal dosages and efficacy, as other investigators ( 31 ) and we have previously reported ( 32 ). Finally, current MR antagonists may not completely block aldosterone effects or concomitant glucocorticoid excess, which can occur in PA ( 13 ).…”
Section: Discussionmentioning
confidence: 57%
“…Evidence indicates that mineralocorticoid receptor antagonists and adrenalectomy achieve similar blood pressure reduction ( 16 ). However, a real word investigation demonstrated that treatment with mineralocorticoid receptor antagonists failed to revert renin suppression in 43% of patients with primary aldosteronism ( 17 ). Failure in renin suppression was associated with enhanced cardiovascular and renal mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Failure in renin suppression was associated with enhanced cardiovascular and renal mortality in these patients. Moreover, 30.7% of treated patients suffered adverse events from spironolactone ( 17 ). A recent study demonstrated that mineralocorticoid receptor antagonists-induced renin suppression was strongly time- and dose-dependent ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure variable of this study was the PRA first measured at least 6 months after the initiation of MRA (post-PRA). Based on the previous studies, 9,10,13,14 posttreatment renin status was defined as unsuppressed (ie, reversal of renin suppression) when post-PRA was ≄1.0 ng/mL per hour and defined as suppressed (ie, remaining of renin suppression) when post-PRA was <1.0 ng/mL per hour. We grouped patients with unsuppressed posttreatment renin into the unsuppressed renin group and those with suppressed posttreatment renin into the suppressed renin group.…”
Section: Exposure Variablementioning
confidence: 99%
“…Some of the important confounders that were not adjusted for in a previous study would include serum potassium and use of beta-blockers, 13 which are associated with both posttreatment renin status and renal function. 14,36,37 To reduce the impact of the confounding by those factors, we adjusted for serum potassium in the main analyses (Table 3) and conducted a sensitivity analysis restricting patients to those who did not use antihypertensive agents that would affect renin status including beta-blockers (Table S3).…”
Section: Original Articlementioning
confidence: 99%